The risk of abdominal aortic aneurysm rupture prediction according to computed tomography data - D. Z. Tutova; R. Sh. Muslimov; L. S. Kokov; L. T. Khamidova; I. P. Mikhailov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Background. Abdominal aortic aneurysm – is a widespread disease, which in some cases does not have any specific clinical symptoms, but possible complications of this pathology are characterized by high mortality. Aortic aneurism rupture is an extremely serious condition that requires emergency surgical treatment. A timely diagnosis of abdominal aortic aneurysm’s rupture risk remains extremely important, since the patient mortality rate is up to 7 times higher when performing an emergency surgery, than when performing a planned surgery. Aim of study: to improve the diagnosis of abdominal aortic aneurysms instability by creating an assessing scale of aortic rupture risk according to computed tomography data. Materials and methods. CT studies were performed by a 160-slice CT scanner and included the native and arterial phases of the scanning. The MSCT data of 179 patients with diagnosed abdominal aortic aneurysm were retrospectively studied, in 46 of whom the condition was complicated by an aortic rupture. CT scans can reveal a number of specific structural changes in the aorta and also surrounding tissues, which can be regarded as aortic wall rupture prediction. That specific structural changes were stratified by severity and the preliminary results were compared with the treatment tactics and the outcome of the disease. Results. The MSCT data of 179 patients with diagnosed abdominal aortic aneurysm shows that the minimum and sufficient set of abdominal aortic aneurysm rupture predictions are: aneurysm size, a sickle sign, aortic wall draping sign, paraaortic fat induration, the thickness of parietal thrombotic masses. The obtained parameters give the possibility to predict the risks of AAA rupture. The prognostic scale is represented by a 4-point scale for assessing aneurysm parameters. Depending on the influence degree of each parameter, it is assigned a number of points corresponding to the level of prognostic significance. The maximum number of risk factors is 17 points. Finding. The assessing scale of the abdominal aortic aneurysm rupture’s risk according to computed tomography data was developed.